2015
DOI: 10.1586/14737175.2015.1103183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cocaine dependence on brain connections: clinical implications

Abstract: Cocaine dependence (CD) is associated with several cognitive deficits. Accumulating evidence, based on human and animal studies, has led to models for interpreting the neural basis of cognitive functions as interactions between functionally related brain regions. In this review, we focus on the magnetic resonance imaging (MRI) studies using brain connectivity techniques as related to CD. The majority of these brain connectivity studies indicated that cocaine use is associated with altered brain connectivity be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 87 publications
2
20
0
Order By: Relevance
“…Repeated experiences over long periods are typically associated to neuronal adaptations [12] and, during craving in addicted individuals, they could manifest as hyper-sensitivity to negative bodily sensations [13]. In this sense, previous research has linked interoceptive processing with insular modulations [3][4][5][6], including both hyper- [6] and hypo-connectivity [3]. In fact, healthy subjects trained to focus attention on the interoceptive domain exhibit modulations of the insula and associated neural systems [12], which may signal an allostatic adaptation following repeated consumption [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated experiences over long periods are typically associated to neuronal adaptations [12] and, during craving in addicted individuals, they could manifest as hyper-sensitivity to negative bodily sensations [13]. In this sense, previous research has linked interoceptive processing with insular modulations [3][4][5][6], including both hyper- [6] and hypo-connectivity [3]. In fact, healthy subjects trained to focus attention on the interoceptive domain exhibit modulations of the insula and associated neural systems [12], which may signal an allostatic adaptation following repeated consumption [7].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, contemporary neurocognitive models have proposed that dopaminergic drug addiction may be crucially related to changes in interoception (namely, the sensing and processing of body signals) given its homeostatic role [1] in the onset and maintenance of addictive behavior [2]. Indeed, drug abusers and consumers present differential activation and/or functional connectivity (FC) patterns involving the insular cortex [3][4][5][6], a putative interoceptive hub [1]. However, extant results are inconclusive (showing both hypo-and hyper-reactivity/connectivity of the insular cortex) and virtually uninformed by relevant behavioral and multimodal neurocognitive measures.…”
Section: Introductionmentioning
confidence: 99%
“…After statistical comparison of the extrinsic connections of the winning model during the non-paretic and paretic CPM, we concluded that three contralateral self-inhibitions (cM1, cS1 and cSMA), one contralateral inter-regional connection (cSMA→cM1), and one interhemispheric connection (cM1→iM1) were significantly different. Some neuroimaging studies reported that during the movement of stroke-affected paretic limbs, a significant neural activity could be observed in the regions of the contralesional hemisphere (Calautti et al, 2007;Ma et al, 2015;Lazaridou et al, 2013;Badillo, Vincent & Ciuciu, 2013;Ward et al, 2003). Nowak et al (2008) demonstrated that overactivity in contralesional M1 occurs early after stroke, affecting the improvement of these brain regions after the vascular incident.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have used functional magnetic resonance imaging (fMRI) to investigate neural reorganization and functional recovery after stroke (Calautti et al, 2007). fMRI univariate analysis of regional activation is valuable for understanding the regional neural substrates associated with cognitive functions (Ma et al, 2015). Using active and passive motion-based fMRI experiments (Lazaridou et al, 2013;Cheng et al, 2012) researchers have typified the post-stroke motor dysfunction and the corresponding potential cerebral reorganization.…”
Section: Introductionmentioning
confidence: 99%
“…Cocaine use disorder (CUD) patients also evidence “heightened coupling” of RSFC signatures, with the amygdala exhibiting stronger connectivity with nodes of the motivational circuitry including the caudate, putamen, nucleus accumbens, and insula (Contreras-Rodriguez et al, 2016; Gu et al, 2010; Konova et al, 2015). Though RSFC has promise for characterizing dysfunctional neural circuitry in addiction, the findings across CUD studies are not always consistent (Ma et al, 2015). Some of the inconsistences may be due to important historical variables such as trauma exposure, a relatively understudied variable in the context of brain imaging in CUD.…”
Section: Introductionmentioning
confidence: 99%